Economics of Tobacco Control : The Maldives - Afaal, Ahmed; Shareef, I. Riaz (World Bank, Washington, DC, 2013)
This paper summarizes briefly the general economic situation in the Maldives and describes its health care system, demographics and health outcomes. Mortality and life expectancy have been improving, but cardiovascular and respiratory diseases and cancers are the top causes of death; smoking is a risk factor for all of them. Tobacco imports have been increasing, although changes in the import duty appears to have caused a significant decrease in 2000. Cigarettes account for most of the tobacco product imports and are smoked by 40 percent of all tobacco product users. Chewing tobacco is also commonly used, by 30 percent of tobacco users. Overall, tobacco use prevalence is high by international standards: in 1997, 57 percent of men and 29 percent of women used some form of tobacco. Prevalence is higher among island communities than in the capital. Prices of cigarettes have been fairly stable, with some price rises from 2000. Government revenues from tobacco import duties have risen, but are less than 2 percent of total import duty revenues. Policy recommendations are to ensure regular real price increases in all tobacco products to deter use, accompanied by actions to detect and deter smuggling, better surveillance and monitoring of tobacco use, improvements in the system of reporting cause of death, and more cessation support to raise quit rates.